PENGARUH INTERVENSI ULTRASOUND THERAPY TERHADAP PENURUNAN NYERI PADA PASIEN PLANTAR FASCIITIS - Mardiana, Tina; Ali, Mohammad; Sariana, Erna (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background: Plantar Fasciitis is a common cause of heel pain that affects almost everyone, both elderly and adults. Plantar fasciitis due to stretching or excessive load on the longitudinal arch or the longitudinal arch. Various efforts have been made to reduce pain in patients with Plantar Fasciitis including physiotherapy using Ultrasound. Data from the Medical Rehabilitation Polyclinic of RSUD dr. Slamet Garut, West Java, in 2020, plantar fasciitis cases reached 173 cases. This study aims to determine the effect of Ultrasound on changes in pain in Plantar Fasciitis patients.The research method: is analytic with a quasi-experimental approach to Pretest-Posttest Group Design, which is to reveal a causal relationship. A sample of 16 people obtained by accidental sampling technique, data was collected using a questionnaire format and then analyzed by paired test. Results: The average pain in Plantar Fasciitis patients before Ultrasound intervention was 60.38 points (moderate pain). The average pain in Plantar Fasciitis patients before Ultrasound intervention was 31.31 points (mild pain). There is an effect of giving Ultrasound on changes in pain in Plantar Fasciitis patients at Dr. Slamet Garut Hospital in 2021 with a p value of 0.001. Conclusion: Giving Ultrasound for six times is effective in reducing pain in Plantar Fasciitis patients